The Effect of Social Media Use on Interest Learning Vocational Students in DKI Jakarta - Wadah, Virahma; Busyra, Nur (research, training and philanthropy institution Natural Aceh, 2024)
Discussing students' interest in social media has pros and cons. Negative perspectives are seen, such as the degradation of learning activities when students access social media daily. Still, other discussions emphasize the importance of social media as a good gap or opportunity for more interactive learning. Interesting to study, this study aims to determine the effect of social media on interest in education. One hundred four respondents (Vocational Students in DKI Jakarta) were recruited to complete the research questionnaire. The research procedure consists of testing the instrument's validity-reliability, classical assumptions (normality and linearity), and simple linear regression analysis (t-test and the coefficient of determination). The study's results accept the alternative hypothesis that